EFEKTIVITAS MEDIA PERMAINAN ULAR TANGGA TERHADAP PENGUASAAN KOSATA BAHASA INGGRIS PADA ANAK KELOMPOK A DI RA NUR AISYAH - Verissa Munandar; Novita Friska (STKIP Subang, 2024)
This research is based on the low level of mastery of English vocabulary among children at RA Nur Aisyah. It can be seen that mastery of English vocabulary is still classified as using methods that are not yet interesting so that children feel bored and end up asking less in English. These limited abilities mean that children are also limited in their vocabulary. To help children learn to master English vocabulary in a fun way, it is necessary to have media that can stimulate children. The aim of this research is to determine the effectiveness of using the snakes and ladders game media on the mastery of English vocabulary in group A children at RA Nur Aisyah. This research uses a quantitative approach with an experimental method with a pre-experimental research design type one group pretest-posttest design. In this study the population was all children in RA Nur Aisyah District. Medan Johor with 57 people. The research sample was group A, the number of students was 20 children. The average result of the pretest was 4.5. After the pretest was carried out, treatment was given in the form of using the snakes and ladders game media on children's English vocabulary mastery. During the treatment, there was an improvement which was visible from the posttest results, where the average was 9.75. To test significance by comparing t0 (“t” count) with tt (“t” table). According to the research results, the value of tcount = 2.231 > 1.729, and dk = (n-1) = (20-1) = 19 and the level is α + 0.05 so it can be concluded that the value of Tcount > Ttable (2.231) (1.729) is obtained. hypothesis H0 is rejected and Ha is accepted. So the alternative hypothesis (ha) is accepted and the null hypothesis (h0) is rejected. So it can be concluded that the snake and ladder game media is effective in mastering English vocabulary